A Study of the Policy Effects of Beijing-Tianjin-Hebei Synergistic Development Strategy on Regional Financial Development: Based on the Synthetic Control Method. (27th October 2022) - Dong, Shugong; Wang, Yaling; Ma, Xiaoyu
Abstract : The Beijing-Tianjin-Hebei (BTH) synergistic development strategy is an important initiative proposed by China to achieve sustainable regional development in order to reduce regional development disparities. Based on the synthetic control method, this article constructs a quasi-natural experiment using Chinese panel data from 2006 to 2020 to empirically test the impact of the event of BTH cooperative development as a national strategy on the financial development of the BTH region in China. It assesses the policy effects of the strategy on three dimensions of financial development as follows: scale, structure, and efficiency. The results of the study show that BTH synergistic development strategy has a positive effect on the scale of finance and effectively controls the financial liquidity risk in the region but has no significant effect on the optimisation of the financial structure. Therefore, it is necessary to take the sustainable development of the region as the premise to continuously promote the BTH regional synergistic development strategy, reduce the difference in financial scale development in the region, construct a financial efficiency evaluation mechanism, optimise the regional financial structure, and finally, achieve the goal of regional financial synergy and regional sustainable development.